(untitled) (Journal of Nobel Medical College, 2020)
Background: Low back pain with or without radiculopathy is most common presentations of chronic pain. Caudal epidural steroid injection is one of the treatment modalities of this type of pain syndromes. Materials and Methods: The study was conducted in 100 patient who presented in our pain clinic. These patients were given caudal epidural steroid injections under fluoroscopy guidance with 60 mg depo-methylprednisolone added to 0.5% lignocaine making a volume of 10 ml. All these patients were asked to follow up at pain clinic at 1 month, 3 months & 6 months to assess the visual analogue scale (VAS) score, Oswestry disability index (ODI), Straight leg Raise test (SLRT) & Patient satisfaction scale. Results: There was significant reduction in VAS score in one month, three months and six months follow up after caudal epidural steroid injection. The 50% reduction in pain was seen in 72 patients, 69 patients and 62 patients in one month, three months and six months respectively. The mean VAS score were 7.84 before pre-injection, 4.32 at one hour, 4.06 at one month, 4.18 at 3 months and 4.64 at 6 months after the procedure.The mean ODI were 35.16 before pre-injection, 32.12 at one hour, 28.14 at one month, 28.57 at 3 months and 28.68 at 6 months after the procedure. Conclusion: Caudal epidural steroid injections causes significant relief in pain symptoms of backache with or without radiculopathy and increases the quality of life.